The Economic Effects Financial Technology (FinTech) Adoption on Small and Medium-Sized Enterprises: Insights from Palembang, Indonesia - Indah Diana; Dewi Sartika (Equity: Jurnal Ekonomi, 2023)
Micro, Small, and Medium Enterprises (MSMEs) are important for This study was conducted to determine how financial technology (Fintech) is used by MSMEs in Palembang City, Indonesia. To manage accounting information, namely to find out the extent to which MSME players have used the benefits of fintech. The respondent population consists entirely of MSMEs in Palembang City, Indonesia. With a total of 100 respondents. This research is a type of quantitative research using primary data obtained from the results of filling out questionnaires. Purposive sampling is used by researchers in relation to sampling strategies, especially MSME players who have used digital payment systems. The data analysis method used in this study to descriptively examine respondents' responses is SEMPLS with the help of SmartPLS software. Based on the research findings, the use of fintech effectively, simply, and without risk has a significant impact on management accounting information. Micro, Small, and Medium Enterprises (MSMEs) are important for This study was conducted to determine how financial technology (Fintech) is used by MSMEs in Palembang City, Indonesia. To manage accounting information, namely to find out the extent to which MSME players have used the benefits of fintech. The respondent population consists entirely of MSMEs in Palembang City, Indonesia. With a total of 100 respondents. This research is a type of quantitative research using primary data obtained from the results of filling out questionnaires. Purposive sampling is used by researchers in relation to sampling strategies, especially MSME players who have used digital payment systems. The data analysis method used in this study to descriptively examine respondents' responses is SEMPLS with the help of SmartPLS software. Based on the research findings, the use of fintech effectively, simply, and without risk has a significant impact on management accounting information.